2020
DOI: 10.7573/dic.2022-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of vibegron versus mirabegron and anticholinergics for overactive bladder: a systematic review and network meta-analysis

Abstract: Background Few randomized controlled trials evaluate the long-term efficacy and safety of pharmacotherapy for overactive bladder (OAB). This network meta- analysis compares the long-term (52-week) efficacy and safety of vibegron, mirabegron and anticholinergics for the treatment of OAB. Methods A systematic literature review and network meta-analysis were conducted following PRISMA guidelines using MEDLINE, Embase and Cochrane Central Register of Controlled Trials and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…There have been several systematic reviews that indirectly compared the efficacy of vibegron and mirabegron. Improvement in daily micturition was similar, but vibegron was associated with significant improvement in total incontinence episodes at week 4 and week 52 as well as voided volume at week 12 and week 52 [21,22]. The most recent systematic review and network meta-analysis concluded that both mirabegron and vibegron were comparable and welltolerated in OAB patients but vibegron might be more effective than mirabegron in improving mean voided volume per micturition [23].…”
Section: Discussionmentioning
confidence: 97%
“…There have been several systematic reviews that indirectly compared the efficacy of vibegron and mirabegron. Improvement in daily micturition was similar, but vibegron was associated with significant improvement in total incontinence episodes at week 4 and week 52 as well as voided volume at week 12 and week 52 [21,22]. The most recent systematic review and network meta-analysis concluded that both mirabegron and vibegron were comparable and welltolerated in OAB patients but vibegron might be more effective than mirabegron in improving mean voided volume per micturition [23].…”
Section: Discussionmentioning
confidence: 97%